Qualidade dos sites na Internet: uma aplicação do modelo WebQual nos hotéis de João Pessoa/PB. - Raposo, Wilker Gomes (2009)
The quality evaluation of the internet sites is today, a topic of study of several researchers worldwide. Different models of sites analyses with diverse central points came up in the academy with focus which alternate themselves between the evaluation of the technological aspects and the quality measurement perceived by the user or consumer. In this research, the WebQual device was used, which was created by Loiacono (2000), and it has the privilege of evaluating the sites quality through the user´s or consumer´s view. The present research aims to evaluate the sites quality of the hotels in the Paraíba capital in the users´perception, and taking into account the WebQual model constructs which are use facility, usage, interactivity and complementary relation. The main factors, present in the sites, were identified in order to find out which ones motivate the users to visit them again. A non-random sample, obtained by the accessibility and convenience criterion was made up with guests and non-guests who are users of the sites, with a total sum of 377 who were interviewed. The survey was carried out by means of structured questionnaire and the results were analyzed through a data descriptive analysis, a confirmatory factorial analysis, a structural equation model technique and multiple linear regression. The constructs demonstrated convergent and discriminatory validity and, compound trustworthiness, in addition to pointing out the positive influence of the utility, of the online operations as well as the entertainment when revisiting the hotel sites. The results obtained by this survey enabled the suggestion of adjustments in the WebQual model for its application.